Bi-directional associations between healthy lifestyles and mood disorders in young adults: the childhood determinants of adult health study - Gall, SL; Sanderson, K; Smith, KJ; Patton, G; Dwyer, T; Venn, A (Cambridge University Press, 2016)
Background Healthy lifestyles prevent cardiovascular disease and are increasingly recognized in relation to mental health but longitudinal studies are limited. We examined bi-directional associations between mood disorders and healthy lifestyles in a cohort followed for 5 years.